A Phenomenological Interpretation of Two-Step Adsorption Kinetics of Humic Acids on Zeolitic Tuff - Luigi Ambrosone; Silvana Canzano; Pasquale Iovino; Stefano Salvestrini; Sante Capasso; Carmine Colella (Adsorption Science & Technology, 2013)
In this study, the kinetics of adsorption of humic acid (HA) from aqueous solution onto a zeolitic tuff were investigated. X-ray diffraction, scanning electron microscopy, porosity and pore-size distribution measurements indicate that macromolecules can diffuse into the material. The kinetic curves show a two-stage adsorption. The adsorbed amount increases up to 2 days, remains constant and then increases again to attain equilibrium. There is a remarkable similarity between this adsorption behaviour of HA on zeolitic tuff and the behaviour observed when ultrathin multi-layers of polymeric materials are fabricated by self-assembly technique. Experiments reveal two distinct stages: the first corresponds to the macromolecules being driven towards the substrate, while the second is the result of arrangement of macromolecules. The first stage is a first-order kinetics with characteristic lifetime of 1–2 days, whereas the second stage is a Johnson–Mehl–Avrami function with (t m ) in the exponential and slower characteristic lifetime.